2018
DOI: 10.3389/fmicb.2018.03090
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Relies on the Heme-Regulated Transporter hrtAB to Resist Heme Toxicity and Uses Heme as a Signal to Induce Transcription of lmo1634, Encoding Listeria Adhesion Protein

Abstract: For pathogenic bacteria, host-derived heme represents an important metabolic cofactor and a source for iron. However, high levels of heme are toxic to bacteria. We have previously shown that excess heme has a growth-inhibitory effect on the Gram-positive foodborne pathogen Listeria monocytogenes, and we have learned that the LhrC1-5 family of small RNAs, together with the two-component system (TCS) LisRK, play a role in the adaptation of L. monocytogenes to heme stress conditions. However, a broader knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 85 publications
(150 reference statements)
2
12
0
Order By: Relevance
“…LAP is a bifunctional, highly conserved alcohol-acetaldehyde dehydrogenase which is essential in promoting the systemic spread of L. monocytogenes during infection (Pandiripally et al, 1999;Drolia et al, 2018). Previous research has demonstrated lap upregulation during nutrient starvation and low glucose (Jaradat and Bhunia, 2002), heme stress (Dos Santos et al, 2018), and oxygen limited environments (Burkholder et al, 2009). In our data, lap was significantly downregulated in both 6179 and R479a with log2fold changes of -5.10 and -2.99, respectively.…”
Section: σ B Genessupporting
confidence: 47%
“…LAP is a bifunctional, highly conserved alcohol-acetaldehyde dehydrogenase which is essential in promoting the systemic spread of L. monocytogenes during infection (Pandiripally et al, 1999;Drolia et al, 2018). Previous research has demonstrated lap upregulation during nutrient starvation and low glucose (Jaradat and Bhunia, 2002), heme stress (Dos Santos et al, 2018), and oxygen limited environments (Burkholder et al, 2009). In our data, lap was significantly downregulated in both 6179 and R479a with log2fold changes of -5.10 and -2.99, respectively.…”
Section: σ B Genessupporting
confidence: 47%
“…A large percentage of these heme-induced genes mapped to orthologues in the ‘transcription’ COG category, suggesting complex transcriptional networks aid in adaptation to this environment by fine tuning gene expression including significant alteration of expression of transcriptional regulators in Sgm . Other bacterial transcriptomes show similar patterns of inducing transcription-related functions in response to blood or heme [1517]. Importantly, we also observed that a selection of Sgm genes induced in response to high heme culture conditions were similarly induced in Sgm that resided within the gut of replete as opposed to starved tsetse flies.…”
Section: Discussionsupporting
confidence: 70%
“…However, both pdu induced and non-induced control cells contain internalin B, Q8Y7G3 encoded putative membrane bound zinc metalloprotease (Lmo1318) involved in release of Q8Y436 peptide pheromone encoding lipoprotein A, PplA (Lmo2637), that conceivably supports activation of PrfA [43, 44], and Listeria Adhesion Protein (LAP, lmo1634), involved in host cell invasion [45], with the latter protein significantly higher expressed in pdu non-induced cells.…”
Section: Resultsmentioning
confidence: 99%